قواعد فقہیہ کے ارتقائی سفر کا تدریجی مطالعہ: THE STUDY OF EVOLUTIONARY DEVELOPMENTS IN ISLAMIC LEGAL MAXIMS - Irfanullah, Dr Hafiz; Masood Qazi, Dr Tahir (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
The juristic maxims have gained current development after taking different evolutionary steps with the passage of time. Earlier, Jurists used the Quran, Hadith, and sayings of pious companions to resolve the issues. This was the informal beginning of juristic Maxims as it is found in the books of Imam Shafi, Imam Abu Yousaf and Imam Muhammad. Later, different jurists used to resolve the social issues. Also, it was observed in the incident of Abu Tahir Dabbas and Abu Saeed Harvi. After this, separate books were compiled on these Maxims. The objective of this study is to highlight the approaches of initial juristic schools of thought. This is qualitative research, and data includes the Quran, Hadith and books of juristic scholars. Hanafi jurists hold a higher status as compared to others. So, for the first time, the practical struggle of Imam Abu Al-Hasan Al-Karkhi appeared. Then, Imam Nasfi explained these Maxims with examples, and Tasees al-Nazar Munsah was compiled. Like this, the work on juristic maxims was started. The work of every jurist was quite different from any other. In some places, these Maxims were explained under Shari’ah objectives but in some ways, these were arranged according to juristic themes. Some scholars arranged these Maxims alphabetically. Some scholars compiled on the base of some special topics. Nowadays, these maxims hold valuable attention from Islamic scholars. So, in different universities, a lot of work has been done on different juristic topics. The basics of these maxims have been highlighted. In Urdu language, a lot of work has been done. Some books have been translated into other languages, especially Mujallah AL-Ahkaam Al-Adliah was translated. Some scholars compiled these Maxims for permanent purposes. They translated them into Urdu and worked on their commentaries.